Konsep Negara Hukum dalam Perspektif Islam dan Indonesia - Ramayanti, Ramayanti; Liulin Nuha, Muhammad; Antasari, Rina (SPT. haria Journal and Education Center Publishing, 2026)
The rule of law is a fundamental concept in the administration of government that places law as the primary foundation in regulating the life of the nation and the state. In Indonesia, the concept of the rule of law is affirmed in the 1945 Constitution of the Republic of Indonesia, which states that Indonesia is a state based on law. Meanwhile, from an Islamic perspective, the concept of the rule of law is reflected in the principles of sharia, justice, deliberation, equality before the law, and the protection of public rights. This article aims to analyze the concept of the rule of law from the perspectives of Islam and Indonesia, as well as to examine the compatibility of the values contained in both systems. This study uses a normative juridical method with statutory and conceptual approaches through library research. The results show that the concept of the rule of law in Islam and Indonesia shares similarities in placing law as the main guideline, upholding justice, and limiting power to prevent arbitrary actions. Although they have different legal foundations and sources, both aim to create order, justice, and welfare for society. Therefore, the values of the rule of law in Islam can serve as a moral and ethical foundation in strengthening the legal system in Indonesia.